2017
DOI: 10.15252/embj.201798004
|View full text |Cite
|
Sign up to set email alerts
|

Topologically associating domains and chromatin loops depend on cohesin and are regulated by CTCF, WAPL, and PDS5 proteins

Abstract: Mammalian genomes are spatially organized into compartments, topologically associating domains (TADs), and loops to facilitate gene regulation and other chromosomal functions. How compartments, TADs, and loops are generated is unknown. It has been proposed that cohesin forms TADs and loops by extruding chromatin loops until it encounters CTCF, but direct evidence for this hypothesis is missing. Here, we show that cohesin suppresses compartments but is required for TADs and loops, that CTCF defines their bounda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

91
874
5
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 714 publications
(975 citation statements)
references
References 96 publications
(215 reference statements)
91
874
5
5
Order By: Relevance
“…Similar auxin‐mediated degradation or conditional genetic deletions of different subunits of the cohesin complex (SMC1A, WAPL, NIPBL, or PDS5) in vivo and in vitro were also performed recently. All converged to the same result: Quantitative elimination of nearly all DNA‐bound cohesin complexes leads to the loss of essentially all “contact domains” that relied on CTCF and cohesin (Haarhuis et al , ; Rao et al , ; Schwarzer et al , ; Wutz et al , ). However, not all chromatin contacts were eliminated: Interactions reminiscent of A‐/B‐compartmentalization were strongly accentuated (Fig ).…”
Section: Ctcf and Cohesin In Insulation Loop Formation And Long‐ranmentioning
confidence: 84%
“…Similar auxin‐mediated degradation or conditional genetic deletions of different subunits of the cohesin complex (SMC1A, WAPL, NIPBL, or PDS5) in vivo and in vitro were also performed recently. All converged to the same result: Quantitative elimination of nearly all DNA‐bound cohesin complexes leads to the loss of essentially all “contact domains” that relied on CTCF and cohesin (Haarhuis et al , ; Rao et al , ; Schwarzer et al , ; Wutz et al , ). However, not all chromatin contacts were eliminated: Interactions reminiscent of A‐/B‐compartmentalization were strongly accentuated (Fig ).…”
Section: Ctcf and Cohesin In Insulation Loop Formation And Long‐ranmentioning
confidence: 84%
“…SCC1‐deficient cells lacked virtually all loops genomewide (Fig A). Cohesin therefore is essential for the formation and/or maintenance of loops (Gassler et al , ; Rao et al , ; Wutz et al , ). Re‐introduction of SCC1 in depleted cells led to the re‐appearance of loops within an hour (Rao et al , ).…”
Section: Genome Organization By Loop Extrusionmentioning
confidence: 99%
“…If cohesin were to form loops through a processive mechanism, the duration with which it entraps DNA may well determine how far loops can be enlarged. Three studies have now tested this hypothesis in different ways (Gassler et al , ; Haarhuis et al , ; Wutz et al , ). WAPL deficiency led to a far longer residence time of cohesin on the DNA.…”
Section: Genome Organization By Loop Extrusionmentioning
confidence: 99%
“…These technologies provided critical insights into key structural and functional components of three-dimensional chromatin organization such as i) A/B compartments (Lieberman-aiden et al 2009), also referred to as compartment domains (Rao et al 2017), which are closely associated with open and closed chromatin domains, respectively; ii) topologically associating domains (TADs) (Dixon et al 2012;Nora et al 2012;Sexton et al 2012), also referred to as contact domains (Rao et al 2017), chromosomal units that spatially constrain cis-regulatory interactions; iii) CTCF loops, also referred to as insulated neighborhoods (Hnisz et al 2016) or loop domains (Rao et al 2017). Interestingly, while these studies suggested a hierarchical domain organization, recent studies based on acute depletion of CTCF or cohesin, or inactivation of the cohesin-loading factor NIPBL, demonstrated that A/B compartments and TADs are not hierarchically organized but represent independent structural (and possibly functional) units of 3D genome organization (Nora et al 2017;Rao et al 2017;Wutz et al 2017;Schwarzer et al 2017). …”
Section: Introductionmentioning
confidence: 99%